Reducing the computational cost of NMR crystallography of organic powders at natural isotopic abundance with the help of 13C‐13C dipolar couplings. (11th March 2019) - Thureau, Pierre; Sturniolo, Simone; Zilka, Miri; Ziarelli, Fabio; Viel, Stéphane; Yates, Jonathan R.; Mollica, Giulia
Abstract: Structure determination of functional organic compounds remains a formidable challenge when the sample exists as a powder. Nuclear magnetic resonance crystallography approaches based on the comparison of experimental and Density Functional Theory (DFT)‐computed 1 H chemical shifts have already demonstrated great potential for structure determination of organic powders, but limitations still persist. In this study, we discuss the possibility of using 13 C‐ 13 C dipolar couplings quantified on powdered theophylline at natural isotopic abundance with the help of dynamic nuclear polarization, to realize a DFT‐free, rapid screening of a pool of structures predicted by ab initio random structure search. We show that although 13 C‐ 13 C dipolar couplings can identify structures possessing long range structural motifs and unit cell parameters close to those of the true structure, it must be complemented with other data to recover information about the presence and the chemical nature of the supramolecular interactions. Abstract : A new DFT free nuclear magnetic resonance crystallography approach is presented, which allows a pool of predicted structures to be screened using 13 C‐ 13 C double‐quantum dipolar curves measured at natural abundance with the help of dynamic nuclear polarization Tested on theophylline, the method was able to identify structures possessing long‐range structural motifs and unit‐cell parameters similar to those of the crystallographic structural database structure, without any structural assumption This approach is expected to considerably simplify the analysis of large structure pools with respect to current computationally‐intensive approaches